PREVALENCE OF TRICHOMONAS VAGINALIS INFECTION AMONG WOMEN IN ERBIL GOVERNORATE, NORTHERN IRAQ: AN EPIDEMIOLOGICAL APPROACH - Nouraddin, Avreen S.; Alsakee, Hadi M. (European Scientific Journal, ESJ, 2015)
Trichomoniasis is one of the sexually transmitted diseases with worldwide prevalence. It is a public health problem and associated with adverse outcomes of pregnancy and increased risk of HIV transmission. This analytic cross sectional study aimed to assess the epidemiological and clinical parameters concerning trichomoniasis in women attended Maternity Teaching Hospital in Erbil over the period from September 2012 till July 2013. Vaginal discharge swabs were collected from 440 women their ages ranged between 16-60 years using randomized sampling method. Out of 440 women, 14 (3.18%) and 12(2.73%) revealed positive results for trichomoniasis using culture technique and direct wet mount, respectively. The infection rate was non-significantly higher among women from rural settings (4.9%) than urban setting people (3.2%) and in housewives (3.8%) more than employed women (1%). Furthermore, Non- pregnant (3.4%) women were more susceptible to infection than pregnant group (0%), and there were no significant differences among married (3.1%), widow (7.7%) and divorced women (0%). Trichomoniasis was comparably higher in illiterate women (4.1%) than those with school and University qualifications (2.44%). A significant proportion of infected women experienced gray colored (50%) vaginal discharge and followed by green colored (16.7%) discharge. The infection rate was 4%, 3.3% and 3.1% among women with age groups of 16-26 years, 27-37 years and 38-48 years, respectively. Furthermore, trichomoniasis was non-significantly associated with number of parity and neonate abnormality. However, it’s significantly (P = 0.016) associated with history of abortion. Moreover, Women who were immediately post menstruation (9.3%) had significantly (P<0.05) higher infection rate than those were at pre- (3.2%), immediately pre- (5.7%) and menses women (0%).